2015
DOI: 10.1002/pds.3904
|View full text |Cite
|
Sign up to set email alerts
|

Medication use for chronic health conditions among adults in Saudi Arabia: findings from a national household survey

Abstract: Compared with the prevalence of CHC in KSA, our study indicates a potential underuse of medications as well as non-adherence to the directions for use. Interventions such as improved clinical guidelines for healthcare providers to increase utilization of necessary medication and educational programs to improve patients' adherence are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Previous evidence demonstrates the underutilization of diagnostic and therapeutic services for diabetes and low quality of care in different countries in the region (4,(11)(12)(13). A national survey in Saudi Arabia, which has the highest burden of diabetes in the EMR, showed that only 42.2% of individuals with diabetes had been diagnosed (15) and that only 70.5% of those known to have diabetes reported taking medication for diabetes (12). In addition to health care services being available, they should be accessible, acceptable, and affordable for communities to benefit from their utilization and experience continuity of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence demonstrates the underutilization of diagnostic and therapeutic services for diabetes and low quality of care in different countries in the region (4,(11)(12)(13). A national survey in Saudi Arabia, which has the highest burden of diabetes in the EMR, showed that only 42.2% of individuals with diabetes had been diagnosed (15) and that only 70.5% of those known to have diabetes reported taking medication for diabetes (12). In addition to health care services being available, they should be accessible, acceptable, and affordable for communities to benefit from their utilization and experience continuity of care.…”
Section: Discussionmentioning
confidence: 99%
“…Also, genetic and epigenetic factors may play a role in the high prevalence of diabetes and its diversity in EMR countries (7). The EMR has high rates of overweight and obesity and inappropriate dietary habits and physical inactivity as the main modifiable risk factors of diabetes (8)(9)(10), as well as underdiagnosis of diabetes, underutilization of health services, and low quality of diabetes care (11)(12)(13). Moreover, millions of displaced people as a result of the armed conflicts have limited access to health services.…”
mentioning
confidence: 99%
“…A multistage stratified probability sample was employed to recruit survey respondents to ensure that the findings of the survey were representative of the Saudi population. A detailed description of the sampling methodology and data collection is available elsewhere . A total of 10 735 individuals aged over 15 were interviewed, with a response rate of about 90% in the SHIS .…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of the sampling methodology and data collection is available elsewhere . A total of 10 735 individuals aged over 15 were interviewed, with a response rate of about 90% in the SHIS . However, this study restricted the analysis to respondents aged between 18 and 80 years to account both for missing data (most respondents aged below 18 had missing observations on some controls) and for low as well as high prevalence of diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…A complex interplay of patient‐ and treatment‐related factors including demographic, socio‐economic, therapy, disease states and health systems and structure determining the allocation of resources, the cost of healthcare and the continuity of care patients receive have been identified to be key influences leading to non‐adherence in patients . Systematic reviews have identified polypharmacy as a factor contributing to medication non‐adherence .…”
Section: Introductionmentioning
confidence: 99%